Post‐diagnosis social networks, and lifestyle and treatment factors in the After Breast Cancer Pooling Project. Issue 4 (8th January 2016) - Kroenke, Candyce H; Michael, Yvonne L.; Shu, Xiao‐Ou; Poole, Elizabeth M.; Kwan, Marilyn L.; Nechuta, Sarah; Caan, Bette J.; Pierce, John P.; Chen, Wendy Y.
Abstract: Objective: Larger social networks have been associated with better breast cancer survival. To investigate potential mediators, we evaluated associations of social network size and diversity with lifestyle and treatment factors associated with prognosis. Methods: We included 9331 women from the After Breast Cancer Pooling Project who provided data on social networks within approximately two years following diagnosis. A social network index was derived from information about the presence of a spouse or intimate partner, religious ties, community participation, friendship ties, and numbers of living relatives. Diversity was assessed as variety of ties, independent of size. We used logistic regression to evaluate associations with outcomes and evaluated whether effect estimates differed using meta‐analytic techniques. Results: Associations were similar across cohorts though analyses of smoking and alcohol included US cohorts only because of low prevalence of these behaviors in the Shanghai cohort. Socially isolated women were more likely to be obese (OR = 1.21, 95% CI:1.03–1.42), have low physical activity (<10 MET‐hours/week, OR = 1.55, 95% CI:1.36–1.78), be current smokers (OR = 2.77, 95% CI:2.09‐3.68), and have high alcohol intake (≥15 g/d, OR = 1.23, 95% CI:1.00–1.51), compared with socially integrated women. Among node positive cases from three cohorts, socially isolated women were more likely not to receive chemotherapy (OR = 2.10, 95% CI:1.30–3.39); associations differed in a fourth cohort. Other associations (nonsignificant) were consistent with less intensive treatment in socially isolated women. Low social network diversity was independently associated with more adverse lifestyle, but not clinical, factors. Conclusions: Small, less diverse social networks measured post‐diagnosis were associated with more adverse lifestyle factors and less intensive cancer treatment. Copyright © 2016 John Wiley & Sons, Ltd.